Intellectualization of Ukraine’s economy: internal determinants and strategic priorities for post-war reconstruction - Ostrovska, Halyna; Sherstiuk, Roman; Ivata, Vyacheslav; Mykhailov, Mykhailo; Pashchenko, Oleksiy; Volska, Olena (Eastern-European Journal of Enterprise Technologies, 2026)
The object of the study is the processes of intellectualization of Ukraine’s economy in the context of post-war reconstruction, structural modernization, digital transformation, and the formation of a knowledge-based economy. The problem addressed in the study is the low efficiency of managing the intellectualization of Ukraine’s economy, which hinders innovation development and European integration. It is substantiated that intellectual potential is a systemic factor of socio-economic development and a key driver of the post-war economic reconstruction of Ukraine. In order to increase the innovation activity of the national economy, a holistic mechanism for the protection and commercialization of intellectual property objects integrated into the state science, technology and innovation policy is formed. A comprehensive political roadmap with cross-sectoral coordination and focus on the synergy of science, business and the state is designed, which allows bridge the gap between knowledge creation and its economic realization. The directions and tools for the effective use of intellectual potential based on its targeted integration with the technological modernization of key sectors of the economy are elaborated. The priorities for the development of the knowledge economy, structured according to sectoral and institutional principles, are substantiated, which made it possible to overcome the dispersion of strategic guidelines for innovation policy. It is pointed out that Ukraine needs to implement smart solutions and consolidate all entities of the national economic system in order to revive at a new higher level of intellectual and socio-economic development. The need for Ukraine’s integration into European value chains was emphasized. Practical application of the results is possible subject to the implementation of comprehensive programs to strengthen the Ukrainian model on the path of an intellectual society in the process of modernization